Maternal cognitive guidance and early education and care as precursors of mathematical development at preschool age and in ninth grade - Anne Sorariutta; Maarit Silvén (John Wiley and Sons Ltd, 2022)
Finnish students' international success in mathematics has been largely explained by the high-quality compulsory basic education system, while increasing evidence suggests that early childhood contexts can also promote development long before formal instruction begins. This study examined, in a sample of 66 mother–infant dyads, 2 early contextual precursors of later mathematical development at preschool age and at the end of comprehensive school. The path analyses showed that maternal autonomy support and scaffolding observed during joint play interactions in infancy, and time spent in various care contexts beyond infancy contributed more to variation in numerical skills than spatial skills tested at preschool age. Maternal autonomy supportive behaviours were related to differences in mathematics and other school grades collected in ninth grade, even after controlling for time spent in various care contexts. Moreover, joint play interactions mediated the relation between mothers' education and children's mathematical outcomes. The findings are discussed in relation to why early developmental contexts can provide an advantageous base for children's mathematical achievement in a society with a high-quality education system.